Vocal and Respiratory Conditioning (CVR) in voice professionals: case studies (Research, Society and Development, 2022)
Introduction: the integration of speech therapy and physical therapy interventions is positive in improving the vocal performance of voice professionals. Objective: to analyze the effects after practice performed through vocal exercises (Semi-occluded Vocal Tract Exercises-SOVTE) and respiratory exercises (use of the Respiron Classic® device). Method: intervention study (pre and post), called Vocal and Respiratory Conditioning (CVR), which included three voice professionals who filled in before and after instruments to assess the self-reported presence of voice handicap (VDI-10), vocal fatigue ( IFV) and symptoms after their presentations (EASE-BR); were evaluated in terms of vocal quality parameters and maximum phonation time; and assessment of respiratory muscle strength and maximum voluntary ventilation. The exercises presented during the meetings were also performed at home, with a record of vocal and respiratory comfort (score from 0 to 10). Data were analyzed descriptively and subjected to statistical tests. Results: the indices referring to the instruments applied showed, in the post-mortem period, less disadvantage and vocal fatigue. The scores given to vocal and respiratory comfort were progressively better during the program (p